2004
DOI: 10.1016/j.ceca.2004.02.003
|View full text |Cite
|
Sign up to set email alerts
|

One-way calcium spill-over during signal transduction in Paramecium cells: from the cell cortex into cilia, but not in the reverse direction

Abstract: We asked to what extent Ca 2+ signals in two different domains of Paramecium cells remain separated during different stimulations. Wild-type (7S) and pawn cells (strain d4-500r, without ciliary voltage-dependent Ca 2+ -channels) were stimulated for trichocyst exocytosis within 80 ms by quenched-flow preparation and analysed by energy-dispersive X-ray microanalysis (EDX), paralleled by fast confocal fluorochrome analysis. We also analysed depolarisation-dependent calcium signalling during ciliary beat rerversal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 72 publications
(132 reference statements)
1
51
0
Order By: Relevance
“…This is in conformance with other EDX analyses, showing spillover in the opposite direction, i.e., into cilia during secretion stimulation [45], and with the occurrence of ciliary reversal in d4-500r cells during exocytosis stimulation [45,46]. Considering this rapid spread of Ca 2+ in either direction we have averaged in our figures all data points recorded along ciliary shafts.…”
Section: Spread Of Ca Kα Signals and Spill-over Phenomenamentioning
confidence: 56%
See 2 more Smart Citations
“…This is in conformance with other EDX analyses, showing spillover in the opposite direction, i.e., into cilia during secretion stimulation [45], and with the occurrence of ciliary reversal in d4-500r cells during exocytosis stimulation [45,46]. Considering this rapid spread of Ca 2+ in either direction we have averaged in our figures all data points recorded along ciliary shafts.…”
Section: Spread Of Ca Kα Signals and Spill-over Phenomenamentioning
confidence: 56%
“…In this case, one has to consider that [Ca] increases may be higher than in electrophysiological recordings. In fact, chemical depolarisation over longer times combined with 45 Ca 2+ flux measurements shows much higher Ca 2+ uptake since Ca 2+ flux into cells (unstimulated background subtracted) lasts much longer than recorded during electrical stimulation [22]. This was explained by masked Ca 2+ flux during ongoing depolarisation [13].…”
Section: Comparison With Electrophysiology and In Vitro Experimentsmentioning
confidence: 97%
See 1 more Smart Citation
“…To us, involvement of some somatic Ca 2+ channels appears appealing, not only because we see a Ca 2+ influx component (Fig. 3 column 1a versus column 3a, and column 1b versus column 3b), but also because in another context we have found that spill-over of Ca 2+ from somatic domains into cilia can easily take place, but not in the opposite direction [18]. One has to recall that we record f/f 0 changes not directly in cilia, but in the nearby cell cortex, as frequently done in work with cilia [5,9,48].…”
Section: Additional New Aspects Of Gtp-mediated Ca 2+ Signallingmentioning
confidence: 99%
“…A reversal reaction is easily observed during depolarization-induced activation of voltage-dependent Ca 2+ channels in the ciliary membrane [15,16]. But spill-over from cortical regions during exocytosis stimulation can also produce ciliary reversal [17,18].…”
Section: Introductionmentioning
confidence: 99%